Prospects and Problems of Medical Tourism in China - Yuaner, MA; Jabar, Juhaini Binti (International Journal of Psychosocial Rehabilitation, 2020)
China has a long history and culture of traditional medicine, along with the increasingly sophisticated Western medical technology, is still seriously underdeveloped in the global healthcare travel industry. A massive population, lastingly uneven distribution of medical resources in the country, and the advancement of medical technology and the affordability of medical procedures in foreign countries, prompt China to become a major medical tourists-generating country for the global business (Pualo., 2018). The global medical tourism market was valued at $53,768 million in 2017 (“The global medical tourism market,” 2019), but China accounted for less than $100 million, lagging far behind other Asian countries including Thailand, India and Malaysia.